Effect of onion compresses on feverish children aged 2-10 months after DPT immunization - Sari, Ria Setia; Ifah Muslimah (Jurnal Keperawatan, 2023)
Introduction: Fever felt by children aged 2-10 months after DPT immunization is caused by the body's reaction to bacteria or viruses that enter the body respondents by injection after vaccination. To overcome this, parents, especially mothers, gave paracetamol drugs, but because of the limited drugs from the Integrated Healthcare Center. Objectives: Knowing the effect of giving shallot compresses on children with fever aged 2-10 months after immunization at Posyandu Kp. Kadu Rt. 003A/001. Methods: This study uses a quasi-experimental design in one pre-test and post-test group. The sample in this study was 60 respondents. The measurement of body temperature before the intervention of giving red onion compresses resulted in hyperthermia of 46 respondents, 76.7%. Whereas after being given the intervention of giving onion compresses, expected results were obtained for 52 respondents 86.7%, and hypothermia for eight respondents 13.3%. This study uses sampling techniques and for this study using random sampling samples. Results: The Wilcoxon Signed Ranks Test Z -5.962ᵇ statistic and the P-value result of 0.000 (<0.05) H0 are rejected. It can be concluded that "Ha is accepted," which indicates the hypothesis is accepted and means there is a difference before and after being given onion compresses. Conclusions: There are differences in the results of the administration of compressed shallots before and after the intervention. From this, it can be concluded that the giving onion poultices are effective in children with fever aged 2-10 months after immunization at Posyandu Kp. Kadu Rt. 003A/ 001.